Toward redressing inequities through partnership: A critical assessment of an equity-focused partnership initiative - Marquis, Elizabeth; Carrasco-Acosta, Emily; de Bie, Alise; Krishna Prasad, Srikripa; Wadhwani, Sneha; Woolmer, Cherie (International Journal for Students as Partners, 2022)
There is growing recognition of the potential for student-faculty/staff partnerships to attend to and redress inequities within postsecondary education. As a result, there are an increasing number of partnership initiatives and programs that foreground principles of equity and justice in their design and delivery. This article reports findings from research that assessed an equity-focused partnership initiative, piloted in 2019, at a research-intensive Canadian institution. We describe the distinctive features of the pilot, including our efforts to enhance equity in and through recruitment and support for student and faculty participants during the pilot, and report findings pertaining to outcomes, process indicators, and positionality and social location. The findings suggest tentatively positive outcomes for participants and contribute to existing scholarship by raising important complexities and limitations relating to issues of access, support, and scale of equity-focused partnerships.